miR-214/199a/199a* cluster levels predict poor survival in hepatocellular carcinoma through interference with cell-cycle regulators - Wang, Peipei (Oncotarget, 2015)
AIMS: To identify the clinical and functional association of miR-214/199a/199a* cluster in human hepatocellular carcinoma (HCC) and to clarify the mechanism of miR-214. METHODS: Kaplan-Meier and Cox proportional regression analyses were used to determine the association of miR-214/199a/199a* cluster levels with the survival of HCC patients. The role of miR-214 in regulating HCC cell proliferation was studied with miR-214 mimics/inhibitor-treated cells. Furthermore, the inhibition effect of miR-214 on E2F2, cyclin-dependent kinase (CDK) 3 and CDK6 expression was assessed in HCC cell lines with miR-214 mimics/inhibitors to increase/decrease miR-214 expression. Direct binding of miR-214 to the 3′-untranslated regions of E2F2, CDK3, and CDK6 was verified by dual-luciferase reporter assay. RESULTS: In analyzing HCC clinical specimens and cell lines, we discovered a uniform decrease in miR-214/199a/199a* expression in comparison with noncancerous tissue or normal liver epithelial cell lines. Higher miR-214 levels were related with improved patient survival. Overexpression of miR-214 in HCC cells inhibited proliferation by inducing G1-S checkpoint arrest. Conversely, RNA interference–mediated silencing of miR-214 promoted cell-cycle progression and accelerated the proliferation of HCC cells. E2F2, CDK3 and CDK6 were each directly targeted for inhibition by miR-214, and restoring their expression reversed miR-214 inhibition of cell-cycle progression. The relationship between expression of miR-214 and its targets was confirmed in HCC tumor xenografts and clinical specimens. CONCLUSIONS: Our results demonstrate that miR-214 has tumor-suppressive activity in HCC through inhibition of E2F2, CDK3 and CDK6.